Pemberian Krim Ekstrak Daun Sukun (Artocarpus altilis )Mencegah Peningkatan Jumlah Melanin Kulit Marmut (Cavia porcellus )yang Dipapar Sinar Ultraviolet B (UVB ) - Riliani, Marisa; Pangkahila, Wimpie; AAGP, Wiraguna (Majalah Kesehatan Pharmamedika, 2017)
Skin is the main target of ultraviolet (UV) ray that result the abnormality of hiperpigmentation. In pathology, hyperpigmentation is caused by an increasing in the amount of melanin. The purpose of this research was to prove the effect of administration of breadfruit leaves extract (Artocarpus altilis) cream prevented the increase of skin melanin in guinea pig (Cavia procellus) exposed to ultraviolet B and to prove the administration of breadfruit leaves extract (Artocarpus altilis) cream have the same effectiveness with 4% hydroquinone cream in preventing the increase of skin melanin in guinea pig (Cavia procellus) exposed to ultraviolet B. This study was a true experimental research using post test only control group design. The subjects were devided into three groups. Group 1 as a control group was treated by UVB exposure and basic cream. Group 2 was treated by UVB and 4% hydroquinone cream. Group 3 was treated by UVB and 3% breadfruit leaves extract cream. There was significant difference within control group compared with group 2 and 3 (p0,05). There was no significant difference within group 2 compared with group 3 (p0,05).The administration of 3% breadfruit leaves extract (Artocarpus altilis) cream prevented the increase of skin melanin in guinea pig (Cavia procellus) exposed to ultraviolet B. The administration of 3% breadfruit leaves extract (Artocarpus altilis) cream had the same effectiveness with 4% hydroquinone cream.